PENGARUH LITERASI KEWARGANEGARAAN TERHADAP IMPLEMENTASI HAK DAN KEWAJIBAN PADA MURID DI SMA NEGERI 1 BELAWANG - Hikmah, Nor; Sarbaini, Sarbaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Civic literacy is a valuable asset in facing the ever-changing advancements and changes of the times. Literacy refers to a process of personal and social transformation (Mohammad Ridwan Saidi, Supriyono, 2022). Civic literacy aligns with the actualization of the values ​​of Pancasila. Pancasila must be implemented in every generation of the nation's behavior and must be actively involved in every aspect of national and state life (Anisa et al., 2021)). Furthermore, the current era of digital globalization has accelerated the transformation of information, which can lead to clashes between religions and cultures within a rapidly developing society. This issue can be addressed by developing cultural and civic literacy in the younger generation. This study used a quantitative approach with a causal associative design. Data were collected through a Likert-scale questionnaire and analyzed using statistical tests. The results showed that the civic literacy of students at SMA Negeri 1 Belawang was quite good, with an average score of 76.59 and a standard deviation of 7.67, indicating a relatively uniform level of student understanding. The implementation of students' rights and obligations also fell into the fairly good category, with an average score of 47.76 and a standard deviation of 5.54, indicating that most students are able to apply their rights and obligations in their daily lives. Furthermore, there was a significant and positive effect between civic literacy and the implementation of students' rights and obligations. This was evidenced by the t-test results, which showed a calculated t-value greater than the t-table (12.878 > 1.985) with a significance level of 0.000 < 0.05. Civic literacy contributed 63.6% to the implementation of students' rights and obligations, while the remaining 36.4% was influenced by factors outside the study. This study emphasizes the importance of improving civic literacy to encourage students to more optimally exercise their rights and obligations as citizens.